Risk in providing accounting services in the context of new regulations regarding liability insurance (OC) in Poland - Świetla, Katarzyna (Copernican Journal of Finance & Accounting, 2015)
In the present economy, it is essential to access to the correct information coming from the market. The source of such information is financial statements of entities, prepared in accordance with accepted accounting principles and ethical behavior requirements. The rapid evolution of solutions conducive to the fulfillment of these expectations requires professionals involved in accounting to engage in continuous learning in order to maintain the high quality of knowledge and experience. Notwithstanding this, correct implementation of separate processes also requires constant cooperation between the customer and the accounting office. Otherwise, both parties are at risk. A way to reduce this risk is mandatory liability insurance (OC) concluded by the accounting service providers in order to protect themselves from the consequences of error and possible claims arising thereof. The paper presents the key issues related to the practical implementation of services in the field of accounting in the modern economy and presents the risks associated with them in the eyes of customers and accounting offices. Against this background, the merits of securing the parties to the concluded contracts in the form of compulsory third party liability purchased by providers is indicated.